Determination of the dependencies of the wear influence of the cylindrical brush on the operational characteristics of the garbage truck’s mounted sweeping equipment - Bereziuk, O.V.; Savulyak, V.I.; Kharzhevskyi, V.O.; Harbuz, Ye. S. (Problems of Tribology, 2023)
The article is dedicated to the establishment of dependencies of the influence of the wear of the cylindrical brush on the operational characteristics of the mounted sweeping equipment of the garbage truck. By using the planning of the second-order experiment with the first-order interaction effects, using the Box-Wilson method, the adequate dependencies of the influence of the wear of the cylindrical brush on the performance characteristics of the mounted sweeping equipment of the garbage truck were determined. It was established that, according to the Student’s criterion, among the investigated factors of influence, the wear of the cylindrical brush has the greatest effect on the deformation of the cylindrical brush, and the width of the contact spot has the least influence. The required pressing force of the cylindrical brush is most affected by the width of the contact spot, and the least by the wear of the cylindrical brush. The response surfaces of the target functions are shown – the amount of deformation and the required pressing force of the cylindrical brush and their two-dimensional cross-sections in the planes of influence parameters, which make it possible to visually illustrate the specified dependences of target function data on individual influence parameters. It was established that the wear of the cylindrical brush of 50% of cases leads to an increase in the deformation of the cylindrical brush by 1.3 times, and the necessary force of pressing of the cylindrical brush – by 3.1...3.6 times, depending on the width of the contact spot. It is shown the expediency of conducting further researches of the effect of antifriction materials on the wear of the friction pairs of the mounted sweeping equipment of the garbage truck.